Behind Soviet barbed wire: to the question of Soviet concentration camps for prisoners of war from the Axis countries in the ESSR in the post-war years. Rec. on the monograph: Khodyakov M. V. Foreign prisoners of the Great Patriotic War in the camps of the NKVD – the Ministry of Internal Affairs of Estonia. 1944–1949 - I. V. Petrov (Омский научный вестник: Серия "Общество. История. Современность")
In the article the analysis of the monograph of professor of St. Petersburg State University, M. V. Khodyakov, devoted to the situation of foreign prisoners of war in the camps on the territory of the Estonian SSR in 1944–1949. The scientific novelty of the research is emphasized, the main content of the monograph is critically analyzed, its merits and fully realized potential research opportunities are noted